Advancing the concept of public goods - Kaul, Inge (Archīum Ateneo, 2003)
Recent decades have seen major shifts in what is considered and treated as private and as public. Economic liberalization, technological advances, and privatization have allowed markets to expand into new product areas and be integrated across national borders. In addition, ever-increasing numbers of private corporations have gone public, floating shares on stock markets. As a result the public—people in generalandshareholders in particular—want to know much more about companies' production and marketing principles. Consumers insist on product labeling. Labor and environmental policies can no longer be hidden behind boardroom doors. Public norms define expected stan-dards. And civil society organizations assess and publicize corporate citizenship (Keane 2001; UNRISD 2000). Moreover, private businesses engage in self-regula-tion, in setting norms and standards, and in arbitrating conflicts—functions usually associated with the state (Cutler, Haufler, and Porter 1999). Meanwhile, government programs increasingly follow market principles, outsourcing service delivery to private providers and recovering costs through user fees and other charges. There are also calls, from businesses and civil society organizations, for governments to operate more transparently and accountably. As the growing literature on good governance signals, the public sector often lacks publicness.